GPS and GSM Based Accident Location Indicator and Rescue System - Poobalan, P.; Naresh, N.; Rajesh, G.; Maheswaran, B.; Vinod, Aswin (Journal of Advance Research in Electrical & Electronics Engineering (ISSN 2208-2395), 2015)
Traffic congestion and tidal flow management were recognized as major problems in modern urban areas, which have caused much crossing for the ambulance. Morethan road accidents in the city have been incessant and to bar the loss of life due to the accidents is even more crucial. To implement this we introduce a scheme called AARS (Automatic ambulance rescuable system). The main theme after this scheme is to provide a smooth flow for the ambulance to reach the hospitals in time and thus minifying the expiration. The idea after this scheme is to implementable an IT’s which would control mechanically the traffic lights in the path of the ambulance. The ambulance is controlled by the central unit which furnishes the most scant route to the ambulance and also controls the traffic light according to the ambulance location and thus reaching the hospital safely. The server also decides the location of the accident spot through the sensor systems in the vehicle which encountered the accident and thus the server walks through the ambulance to the spot. This scheme is fully automated hence it finds the accident spot, controls the traffic lights, serving to reach the hospital in time.